2011
DOI: 10.4028/www.scientific.net/ddf.312-315.240
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Modeling of Silicon Transport into Germanium Using a Simplified Crystal Growth Technique

Abstract: A numerical simulation study, using finite element method, was carried out to examine the temperature and concentration fields in the dissolution process of silicon into germanium melt. This work utilized a simplified configuration which may be considered to be similar material configuration to that used in the Vertical Bridgman growth methods. The concentration profile for the Si-Ge sample processed using this technique shows increasing transport silicon into the melt with time, moreover, a flat stable interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Vynnycky and Kimura [92] simulated the solidification and phase change in the presence of convection by using both numerical and analytical techniques. Mechighel et al [93] carried out a 2-D numerical simulation to study the velocity, temperature, and concentration distribution in the dissolution process of silicon into a germanium melt by utilizing the vertical Bridgman method. They showed that gravity has a strong effect on the shape of the interfaces and showed the transport becomes convection dominated when gravity is present.…”
Section: Solidificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Vynnycky and Kimura [92] simulated the solidification and phase change in the presence of convection by using both numerical and analytical techniques. Mechighel et al [93] carried out a 2-D numerical simulation to study the velocity, temperature, and concentration distribution in the dissolution process of silicon into a germanium melt by utilizing the vertical Bridgman method. They showed that gravity has a strong effect on the shape of the interfaces and showed the transport becomes convection dominated when gravity is present.…”
Section: Solidificationmentioning
confidence: 99%
“…F. Mechighel et al [118] performed a numerical simulation to analyze the temperature and concentration behaviour in the separation process of silicon into molten germanium. They used a simplified arrangement similar to the materials arrangement used in the vertical Bridgman growth technique.…”
Section: Solidificationmentioning
confidence: 99%
“…Vynnycky and Kimura [92] simulated the solidification and phase change in the presence of convection by using both numerical and analytical techniques. Mechighel et al [93] carried out a 2-D numerical simulation to study the velocity, temperature, and concentration distribution in the dissolution process of silicon into a germanium melt by utilizing the vertical Bridgman method. They showed that gravity has a strong effect on the shape of the interfaces and showed the transport becomes convection dominated when gravity is present.…”
Section: Solidificationmentioning
confidence: 99%
“…F. Mechighel et al [118] performed a numerical simulation to analyze the temperature and concentration behaviour in the separation process of silicon into molten germanium. They used a simplified arrangement similar to the materials arrangement used in the vertical Bridgman growth technique.…”
Section: Solidificationmentioning
confidence: 99%
“…Natural convection may be also present in some of the crystallisation processes, [20][21][22][23][24][25][26][27] which is the subject of our other work to be published separately. In solidification of binary molten alloys, all phenomena involved in heat transfer of a binary alloy without solidification is present as well as the solidification process, which is the last stage.…”
Section: Introductionmentioning
confidence: 99%